Impact of Pay-What-You-Want Pricing Model. - Lightwala, Owais; Wall-Andrews, Charlie (Journal of Arts Management, Law & Society, 2024)
Study investigates the effectiveness of Pay-What-You-Want (PWYW) pricing models in the nonprofit performing arts sector, focusing on Toronto's Harbourfront Centre during the COVID-19 pandemic. Through methods involving quantitative ticket sales data and qualitative insights from management, this research assesses how PWYW affects audience behavior, revenue, and accessibility. Results indicate that PWYW can enhance audience inclusivity, notably by attracting a broader geographic distribution of attendees, though shifts in demographic diversity were less pronounced. Analysis of repeat customers reveals increased financial contributions under PWYW, suggesting the model's potential for leveraging loyal patron support. The study provides strategic implications for arts organizations, emphasizing the need for comprehensive audience analysis and targeted marketing to maximize PWYW's accessibility and sustainability goals. Findings contribute to the literature on alternative pricing in arts management, highlighting PWYW's viability as a tool for democratizing access while maintaining financial resilience post-pandemic.